Дослідження фармакологічного потенціалу 1-алкілпохідних 3,5-диметил-4-((4-нітробензиліден)аміно)-1,2,4-тріазолій броміду - Панасенко, Олександр Іванович; Британова, Тетяна Сергіївна; Гоцуля, Андрій Сергійович; Panasenko, O. I.; Brytanova, T. S.; Hotsulia, A. S. (Запорізький державний медико-фармацевтичний університет, 2024)
Мета роботи – предиктивне визначення потенціалу створення біологічно активної субстанції з протигрибковою дією на основі 1-алкілпохідних 3,5-диметил-4-((4-нітробензиліден)аміно)-1,2,4-тріазолій броміду. Матеріали і методи. Прогнозування токсичності ряду сполук здійснили, використавши програму TEST (Toxicity Estimation Software Tool), за допомогою якої визначили предиктивний рівень гострої токсичності, екотоксичності та мутагенності. Прогнозування фізико-хімічних, фармакокінетичних параметрів, а також оцінювання лікоподібності та доступності речовин здійснили, застосувавши онлайн ресурс SwissADME. Найсприятливішу просторову конфігурацію ліганду щодо активної ділянки білка визначили, використавши обчислювальний метод молекулярного докінгу, крім того, оцінили силу їхньої взаємодії. Підготовка лігандів відбувалась із застосуванням програмного фунціоналу MarvinSketch 6.3.0, HyperChem 8 та AutoDock Tools-1.5.6. Підготовка модельного ензиму передбачала використання програмних продуктів Discovery Studio 4.0 та AutoDock Tools-1.5.6. Практичну реалізацію гнучкого молекулярного докінгу здійснили, залучивши програмні інструменти платформи AutoDock/Vina. Результати. У процесі поетапного прескринінгу сформованих структур ряду 1-алкілпохідних 3,5-диметил-4-((4-нітробензиліден) аміно)-1,2,4-тріазолій броміду отримали низку якісних і кількісних показників, що пов’язані з фізико-хімічними характеристиками та фармакокінетичними параметрами речовин, які дослідили. Згідно з результатами першого етапу досліджень, аналізовану групу речовин можна можна предиктивно вважати малотоксичною, але з високим ризиком проявлення мутагенних властивостей. На наступному етапі роботи, який передбачав аналіз фізико-хімічних показників, фармакокінетичних параметрів, загальної лікоподібності та біодоступності, 1-алкілпохідні 3,5-диметил-4-((4-нітробензиліден)аміно)-1,2,4-тріазолій броміду визначені як речовини з досить позитивним фармакологічним профілем. The aim of the work is to preliminary determine the potential for creating a biologically active substance with antifungal action based on 1-alkyl derivatives of 3,5-dimethy-l-4-((4-nitrobenzylidene)amino)-1,2,4-triazolium bromide. Materials and methods. The toxicity of the studied compounds has been predicted using the TEST program (Toxicity Estimation Software Tool), which allowed to determine the predictive level of acute toxicity, ecotoxicity and mutagenicity. The physicochemical and pharmacokinetic parameters have been predicted, and the drug-like properties and availability of the investigated substances have been assessed using the online resource SwissADME. The determination of the most favorable spatial configuration of the ligand relative to the active site of the protein and the assessment of the strength of their interaction have been realized using the computational method of molecular docking. The ligands have been prepared using MarvinSketch 6.3.0, HyperChem 8 and AutoDock Tools-1.5.6 software. The preparation of the model enzyme has been based on the use of Discovery Studio 4.0 and AutoDock Tools-1.5.6. The practical implementation of flexible molecular docking has been carried out using the software tools of the AutoDock/Vina platform. Results. In the process of step-by-step prescreening of the formed structures of a number of 1-alkyl derivatives of 3,5-dimethyl-4-((4-nitrobenzylidene) amino)-1,2,4-triazolium bromide, a number of qualitative and quantitative indicators related to the physicochemical characteristics and pharmacokinetic parameters of the studied substances have been obtained. According to the results of the first stage of research, the group of substances under consideration can be predictively considered low-toxic, but with a high risk of mutagenic properties. The next stage of the work, which involved the analysis of physicochemical parameters, pharmacokinetic parameters, general drug-like properties and bioavailability, allowed us to identify 1-alkyl derivatives of 3,5-dimethyl-4-((4-nitrobenzylidene)amino)-1,2,4-triazolium bromide as substances with a rather positive pharmacological profile. The final stage in the form of molecular docking of the structure of the studied compounds to the active site of lanosterol 14α-demethylase allowed us to determine the nature of the chemical interaction and the type of amino acid residues that may be involved in the antifungal properties of the key ligands. The analysis of the docking results allows us to determine the privileged nature of the nonyl substituent at the first Nitrogen atom of the 1,2,4-triazole synthon in the structure of the presented series of compounds for the formation of antifungal properties.
Research on the pharmacological potential of 1-alkyl derivatives of 3,5-dimethyl-4-((4-nitrobenzylidene)amino)- 1,2,4-triazolium bromide
Панасенко О. І. - ORCID ID: 0000-0002-6102-3455; Британова Т. С. - ORCID ID: 0000-0003-1805-4552; Гоцуля А. С. - ORCID ID: 0000-0001-9696-221X.
Keywords: 4-аміно-1,2,4-тріазол; дизайн; токсичність; ADME-аналіз; молекулярне моделювання; 4-amino-1,2,4-triazole; design; toxicity; ADME analysis; molecular modeling